Analisis Perbandingan Pendapatan usaha home industri kerupuk tepung dan emping melinjo di Desa Pulo Pisang Kecamatan Pidie Kabupaten Pidie - Muhammad Azrul; Edy Marsudi; Mustafa Usman (Jurnal Ilmiah Mahasiswa Pertanian, 2016)
ANALYSISBENEFIT SALES OF HOME INDUSTRY ON MELINJO AND FLOUR’S CHIPS IN PULO PISANG PIDIE CITY Muhammad Azrul/Agribussines Unsyiah ABSTRACT Flour crackers are traditional processed products using starch and wheat flour as the main ingredient. Melinjo is one of the flagship products of Pidie, which is produced in almost all districts. This study aimed to analyze whether the home business industry can provide benefits and do a comparison of income. The analytical method used in this research is the analysis of income, ravenue cost ratio, BEP and comparative analysis. The survey results revealed that businesses Home Industry cracker flour and melinjo can provide benefits and melinjo business is more profitable than business of flour cracker. keywords  : flour crackers, melinjo crackers, analysis income, comparison of income